Pembentukan Karakter Anak yang Disiplin dan Berbudi melalui Pengenalan Dasar Manajemen, Hukum, dan Tekhnologi Informasi - L. Jatmiko Jati; Adinda Mutia Gani; Syafira Mahfuzi Ardiyati; Nola Amelia Zalmy; Da’iah Amelia Sukandy (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Referring to three missions of higher education (Tri Dharma Perguruan Tinggi) which included education, research and, and community service. So universities can carry out these dharma functional and integrated way. Devotion among the community as one of dharma college occupying a position a strategic way to maintain and improve the quality of the lives of the community educate for. The program authority is called the formation of the character of a child who disciplines and refinement with the introduction of the base of management, law, information technology and education. The form of this program is to introduce of the surrounding area on the students of the fundamental to the kindergarten school Doremi in Mataram City as discipline, savings and socialization of the negative impact of gadget. One of the objectives this program is to manifesting the character discipline and a good social interaction from preschool children.